Exploration of the visual streak of the Mongolian gerbil as a model for the human central retina - Günter, Alexander; Jarboui, Mohamed Ali; Mühlfriedel, Regine; Seeliger, Mathias W. (Frontiers in Medicine, 2025)
IntroductionThe Mongolian gerbil (MG), a day-active rodent, features a particular retinal region of high visual acuity, the visual streak (VS). Optimized for vision in desert-like environments, the VS allows for a perfect view of the horizon between the projection areas of the sky and the ground. Here, we assess the structural basis of this specialized region and compare the findings to the conditions at the human retinal center.MethodsThe VSs of MG retinas (n = 5) were evaluated morphologically with immunohistochemistry for cone, rod, and RPE cell-specific markers in dorsoventral cross-sections, and the results were compared to data from the near (adjacent) and far periphery. Mass spectrometry of the VS and peripheral retina/RPE was used to analyze the proteomic differential expression between these regions.ResultsIn the VS of the MG, we found an increased density of cones, elongated photoreceptor outer segments (OSs), and a rod-to-cone ratio lying within the zone of descent between the border of the macula and the fovea (macular shoulder). Similarly, the base area of retinal pigment epithelium (RPE) cells in the VS was significantly reduced, while cells were taller than those in the periphery. Accordingly, proteomic data provided evidence for an enhanced abundance of key proteins relevant to photoreceptor and RPE function and pathophysiology of macular diseases in the VS.ConclusionThe high degree of conformance between the VS data of the MG and the human central retina renders the MG a promising rodent, non-primate model of the central human retina.